PERAN SERTA MASYARAKAT DALAM UPAYA PENGURANGAN SAMPAH DI KELURAHAN PANARUNG, KECAMATAN PAHANDUT, PALANGKA RAYA, KALIMANTAN TENGAH DENGAN METODE DAUR ULANG - Yayok Suryo Purnomo; Rexy Ronaldo Tiong (EnviroUS, 2021)
Along with the increase in population and consumption pattern, they cause increase in waste volume, types, and characteristics. All this time, most of the society consider waste as unworthy leftovers and useless. At this study location, Panarung Sub District RW XIV, has limitation in waste treatment because facilities provided are not adequate and lack of awareness from the community. Dominating wastes in this study location are organic wastes such as food waste and leaves, plastic, and paper wastes as well. Aims of this study are to find out waste treatment activity’s driving factors, and community’s awareness towards the environment’s quality at Kelurahan Panarung RW XIV. Datas obtained from this study will be given in form of tables, charts, and will be analyzed through Minitab Software for correlation analysis. This study has been conducted for 14 days at Panarung Sub District RW XIV, and it is known that local communities do waste sorting and recycling. The results obtained are, waste generation before being sorted is 303,5 kg and after being sorted it is reduced to 185,55 kg. From the sorting activity, it is known that the mean of waste generation reduction is 38,86%.